Income Taxes, Gross Hourly Wages, and the Anatomy of Behavioral Responses: Evidence from a Danish Tax Reform - Kazuhiko Sumiya; Jesper Bagger (Institute of Labor Economics (IZA), 2022)
This paper provides quasi-experimental evidence on the effects of income taxes on gross hourly wages by utilizing administrative data and a tax reform in Denmark. The reform introduced joint taxation to a middle tax bracket, bringing large changes to the tax system facing married couples. Using variation in spousal income for identification, we present non-parametric graphical evidence based on a difference-in-differences design among working married males. First, we find hetero- geneous effects across income levels. For low-income workers, taxes have negative and dynamic effects on wages. Their elasticity of wages (with respect to net-of-marginal-tax rates) is close to one. For higher-income workers, the effects are small and static, with an elasticity of approximately 0.2. Second, wages respond to taxes through human capital accumulation and job changes. Finally, with smaller magnitudes than wages, daily hours worked also respond negatively to taxes, which contrasts with the prediction from a standard labor supply-and-demand model.
Keywords: H22; H24; J22; J24; J30; J62; 330; income taxation; administrative data; tax reforms; difference-in-differences; gross hourly wages; labor supply; human capital accumulation; job changes